Overview Inklusi Keuangan; Studi Literasi Keuangan Syariah Terhadap Masyarakat. - Irvan Dian Budianto (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2022)
Public literacy in Islamic finance is still relatively low, especially in the Islamic banking sector. This causes the market share of Islamic banking to be 5.95 below that of conventional banking. This research topic focuses on the issue of positive or negative influence between Islamic financial inclusion and Islamic financial literacy. In addition, the application of sharia principles is also related to issues that affect sharia financial inclusion. Exposure to sharia literacy and sharia principles has not yet touched all levels of society. The use of Islamic banking services is still not based on these two factors.